(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Gestational diabetes mellitus (GDM), a common metabolic complication of pregnancy, carry an increased risk of adverse pregnancy outcomes for both mothers and their offspring in every population. Although several risk factors are in common for every population, some risk factors differ from population to population. The present study was therefore designed to determine the risk factors of GDM in the context of Bangladeshi population. Methods: The present case-control study was conducted in the BIRDEM-2 General Hospital, Dhaka over a period of 2 months from November 2021 to December 2021. Pregnant women with confirmed GDM at their 2nd and 3rd trimesters (above 12 weeks of gestation) were taken as case (n = 31) and normal pregnant women at their 2nd and 3rd trimesters were included as control (n = 35). Pre-pregnancy diabetes, multiple gestation, unexplained abnormal pre-pregnancy body mass index, pregnant women in labor, or with chronic diseases, such as, tuberculosis, malignancy, renal failure, congestive heart failure, and advanced liver failure, and any other serious illnesses were excluded from the study. While the outcome variable in the present study was GDM, the exposure variables were grouped into demographic variables (age, residence, occupation and socioeconomic status), BMI, obstetric and reproductive characteristics (gestational age, gravida, parity, age at menarche, age at first pregnancy), pertinent past history (pre-pregnancy obesity, family history of Type-II diabetes), current obstetric history (polyhydramnios and UTI). A 2 h diagnostic 75 g oral glucose tolerance test (OGTT) was performed after an 8–12 hour overnight fast according to WHO Criteria. The diagnosis of GDM was made when at least one of the two oral GTT values were raised: fasting blood glucose > 95 mg/dl (5.3 mmol/L), of 2 h postprandial glucose ≥ 140 mg/dl (7.8 mmol/L). Result: The present study demonstrated that GDM cases were on an average 3.2 years older than the normal pregnant women (p = 0.010). They were also heavier than the control women in terms of BMI (p = 0.094). The history of Type-II diabetes in the first-degree relatives of GDM women was significantly higher than that in the non-GDM (p < 0.001). Hypertensive disorders in the present pregnancy and previous history of preterm birth showed their significant presence in the GDM group than those in the control group (p = 0.013 and p = 0.044 respectively). The history spontaneous abortion in previous pregnancy was considerably higher in the former group than those in the latter group. Conclusion: The study concluded that advanced maternal age, overweight and obesity, history of Type-II diabetes in the first-degree relatives of GDM women, hypertensive disorders of pregnancy in the current pregnancy and past history of preterm birth are the significant risk factors for GDM. Ibrahim Card Med J 2021; 11 (2): 27-32